Screening of Bioactive Compounds of Gambir leaf (Uncaria gambir Roxb) as Antibiofilm Againts the Glucosyltransferase of Streptococus mutans Enzyme - Khalid, Idham; Sari, Dea Kurnia; Bakri, Muttaqien; Daniel, Daniel; Frengki, Frengki; Makmur, Ali; Riandi, Lian Varis; Ferdian, Riyan; Amiruddin, Amiruddin (Universitas Syiah Kuala, 2024)
The use of natural ingredients in dental care, such as manginang which has become part of the Minang community culture, is considered an alternative dental care that must be created to overcome the negative impacts of dental care made from artificial materials. The core of this study is to change the manginang tradition towards logical verification through screening of bioactive compounds of gambir leaves (Uncaria gambir Roxb.) as antibiofilms against Streptococcus mutans. This study was conducted using an in silico strategy approach with the help of computer programs such as MOE v.09 and Chimera 1.13.1, as well as the Way2Drug site, protein information bank, and protox_ii. This study began with the collection of ligand information from the writing, followed by transformation into 2D and 3D designs. Other antibiofilm actions were decided using the QSAR procedure through the website (http://www.way2drug.com/PASSOnline/predict.php). The selected antibiofilm compounds were then followed by observing their affinity for the receptor (pdb id. 3AIB) using an atomic docking strategy. Finally, the ligand damage profile was observed to anticipate. The results of this study indicate that of the 41 identified gambir leaf compounds, there are 20 compounds that have the potential to have antibiofilm effects with quinnic acid having the highest score (Pa 0.703), while the compound with the strongest affinity for the receptor is chlorogenic acid with an affinity score (Gbinding) of -16.03 kcal/mol and an average of low toxicity (level IV-VI). However, of the 20 bioactive compounds of gambir leaves, only 5 compounds are predicted to have the same potential as the -maltose control.